PENGELOLAAN PROGRAM PENDIDIKAN KESETARAAN PAKET B DI PKBM INSAN CENDEKIA TAMPAN KOTA PEKANBARU - Zakia Dela Putri; Daeng Ayub Natuna; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to find out how the management of the Package B Equality Education program works in Pekanbaru's PKBM Tampan Insan Cendekia. This study uses a descriptive method with a qualitative approach. The research subjects in this study were 4 people: the technique of collecting data using questionnaires. Data analysis techniques using Triangulation. The results of this study show that the planning in the acceptance system of citizens studying at PKBM Insan Cendekia is open, this institution has fulfilled the identity in PKBM which is seen as a notarial deed, the recruitment of teachers is concluded by making good friends. let know that this PKBM is looking for teachers, determining the place of learning seen from the building where the learning is still renting a store, the source of money from the education office of the city of Pekanbaru, the manager of socialization programs in PKBM by distribute and via social media. The implementation in PKBM comes from the learning population that registered 31 people, but only involves 15 people in the learning process who come more when they want to take the exam, while teachers at this institution have obtained educational qualifications that undergraduate education and teaching according to the subjects are not all teachers are based on teacher training, learning is done face-to-face once a week and teachers follow adult education. Evaluation The subjects given by teachers are tested in UNPK according to graduation standards. Teachers know the results of learning by performing daily tests, if the value of the learning community does not reach the maximum, the tutor tries to motivate the students to learn materials that they do not understand.Key Words: Management, Equality Package Education Program B